PENGEMBANGAN BAHAN AJAR ANEKDOT INTERAKTIF MENGGUNAKAN APLIKASI FLIPGRID UNTUK MENINGKATKAN KEMAMPUAN BERBICARA SISWA - Afina Zatil Isnan Maruhawa; Ayu Wandira Br Sitepu; Eniya Rianta Sema Kudadiri; Rani Citra Lestari Zai; Sheilla Valensia Girsang; Yolanda Vera Nicole Sitinjak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop interactive anecdote-based teaching materials using the Flipgrid application through the ADDIE development model and to evaluate their effectiveness in improving high school students’ speaking skills. The main challenges in anecdote learning include students’ limited ability to understand implicit criticism and their lack of readiness to present anecdotal texts orally. This research employed a qualitative descriptive method supported by classroom observations, teacher interviews, documentation of students’ Flipgrid video recordings, researchers’ reflective notes, and a perception questionnaire administered to 15 students. The developed materials consist of a learning module, video models, script-writing guidelines, recording instructions, and a performance rubric. The results indicate that Flipgrid significantly enhanced students’ speaking fluency, intonation clarity, expressive gestures, and self-confidence. Questionnaire data reinforced these findings, showing high approval rates for improvements in fluency (86%), confidence (80%), multimodal expression (93%), and usability of the teaching materials (90%). Furthermore, Flipgrid’s re-recording feature and peer feedback fostered a reflective and collaborative learning environment. Overall, the interactive materials proved effective in supporting speaking skill development and align with the principles of the Independent Curriculum, which emphasize creativity, authentic learning experiences, and project-based performance.